2015
DOI: 10.1007/s12288-015-0513-6
|View full text |Cite
|
Sign up to set email alerts
|

Growth in Children Treated for Acute Lymphoblastic Leukemia: Single Institution Report from North India

Abstract: Survivors of childhood leukemia are at risk of impaired growth and short stature as adults due to intensive combination chemotherapy and radiation injury. This study was undertaken to evaluate anthropometry in children treated for acute lymphoblastic leukemia (ALL). Children treated for ALL and off treatment for a minimum period of 2 years were evaluated for height, weight and BMI. Z scores were calculated for height, weight and BMI: at induction, 6 months after starting treatment, at end of treatment and at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12][28][29][30][33][34][35][36][37] Our study suggests a significant growth impairment which is already noticeable 6M after the beginning of treatment with a minimum HP reached at 12M, confirming a previously reported early detrimental effect of the treatment on height. 12,28 Our data further characterize linear growth throughout the treatment period, showing a persistence of the impact on height until the end of treatment as no significant catch-up growth could be found until 24M after diagnosis. A significant recovery of linear growth started only at the end of treatment, at 48M after diagnosis, as documented by other reports.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][28][29][30][33][34][35][36][37] Our study suggests a significant growth impairment which is already noticeable 6M after the beginning of treatment with a minimum HP reached at 12M, confirming a previously reported early detrimental effect of the treatment on height. 12,28 Our data further characterize linear growth throughout the treatment period, showing a persistence of the impact on height until the end of treatment as no significant catch-up growth could be found until 24M after diagnosis. A significant recovery of linear growth started only at the end of treatment, at 48M after diagnosis, as documented by other reports.…”
Section: Discussionsupporting
confidence: 89%
“…The increased risk of impaired linear growth and obesity/overweight has been largely studied over the past decades to determine whether these adverse outcomes are predictable and potentially reversible. [5][6][7][8][9][10][11][12][14][15][16][17][18][19][20][21][22][23][24] Published results are conflicting and, in some cases, difficult to interpret considering the heterogeneity of therapeutic protocols in use. In recent decades, cranial radiotherapy (CRT) has mostly been replaced by intrathecal chemotherapy as the standard central nervous system prophylaxis and treatment, resulting in less sequelae related to this treatment modality.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, Kumar et al [4] investigate growth impairment and short stature among children treated for acute lymphoblastic leukemia, while Rohilla et al [5] report on obstetric outcomes in women with chronic myelogeneous leukemia. Another tricky management issue is the judicious management of elderly AML or high-risk MDS, and this is addressed by a Turkey study which looks at epigenetic modifiers alone as well as in combination with low-dose cytosine arabinoside in such patients.…”
mentioning
confidence: 99%
“…This finding is consistent with previous studies 22,24‐27 that reported a decrease in height during the period from diagnosis until the end of therapy as one of the negative sequelae of chemotherapeutic treatment that was observed in children diagnosed with ALL in early childhood. The first decrease in height was detected six months after the beginning of treatment, which may affect the final height after completion of therapy 22,24 . Leone et al 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The first decrease in height was detected six months after the beginning of treatment, which may affect the final height after completion of therapy. 22,24 Leone et al 28 reported that ALL survivors were significantly shorter than the control group with no difference regarding weight or BMI.…”
Section: Discussionmentioning
confidence: 99%